Low Compliance in a Health‐Conscience Spending Era Likely Helps Obviates the Need for 6 month BI‐RADS 3 Breast MRI Follow‐up After 1 year. Issue 5 (1st March 2017) - Mosier, Andrew; Gupta, Esha; Ataya, Dana; Bhatt, Kavita; Rim, Alice
Abstract: The goal of our IRB‐approved study was to assess if a follow‐up MRI every 6 months for 2 years is the most appropriate short‐interval follow‐up schedule. 203 breast MRI exams were performed from October 2009 to January 2014 as part of a BI‐RADS 3 follow‐up representing 2.6% of all breast MRIs (7, 822) performed. We performed a retrospective longitudinal medical records review of compliance; malignancy rate of BI‐RADS 3 exams; and average time and number of breast MRIs necessary prior to definitive disposition. While 77.8% eventually returned, only 45.5% of patients were compliant with follow‐up at or near 6 months (4.5–7.5 months). Of those who eventually returned, it took an average of 1.31 follow‐up MRIs (95% CI: 1.20–1.43 exams) and 10.3 months (95% CI: 9.0–11.7 months) before definitive disposition. 93.5% of initial findings were dispositioned as benign after two follow‐up MRI exams (malignancy rate: 0.98%). Our results lend support to the possibility that the follow‐up interval for BI‐RADS 3 breast MRIs could be lengthened to 12 months if additional follow‐up MRIs are necessary after the first year of 6‐month follow‐up breast MRIs. Foremost, this appears to be a safe follow‐up alternative since benign definitive disposition can usually be made in less than 1 year. Supplemental reasons include persistent low‐patient compliance (as redemonstrated in our study) and the higher cost of breast MRI compared to mammogram/ultrasound follow‐up. Finally, this paper's findings further support the suggested MRI follow‐up interval in the newest BI‐RADS atlas.